Association between reduced heart rate variability components and supraventricular tachyarrhythmias in patients with a systemic right ventricle - Zandstra, Tjitske; Kiès, Philippine; Maan, Arie; Man, Sum-Che; Bootsma, Marianne; Vliegen, Hubert; Egorova, Anastasia; Mertens, Bart; Holman, Eduard; Schalij, Martin; Jongbloed, Monique (Autonomic neuroscience, 2020)
Patients with a systemic right ventricle are prone to develop heart failure. Abnormal heart rate variability (HRV), a measure of autonomic dysfunction, is associated with morbidity and mortality in patients with left ventricular failure. The association between HRV and supraventricular arrhythmias (SVTs), which are associated with adverse events in this population, was assessed. 24-Hour Holter recordings of patients with a systemic right ventricle and healthy controls were analysed in a retrospective cohort study. HRV was calculated and compared between groups. Correlation coefficients were determined for HRV variables and clinical characteristics. The relation between HRV and SVTs was investigated with linear regression. The patient group included 29 patients (69%) late after Mustard or Senning correction for transposition of the great arteries, and 13 patients with congenitally corrected transposition of the great arteries (31%). The control group included 38 subjects. HRV was significantly lower in patients compared with controls. In the patient group, lower SDANN (standard deviation of the average NN intervals calculated over 5-minute intervals) was independently associated with a higher number of supraventricular arrhythmias (95% CI −0.03 to −0.0004, p = 0.045). In exploratory correlation analysis, several HRV variables correlated with echocardiographic systemic right ventricular function (rho = 0.36, p = 0.02 for SDANN), and exercise capacity (rho = 0.39, p = 0.05 for SDANN). In patients with a systemic right ventricle, HRV is lower compared with controls and (SDANN) is independently associated with supraventricular arrhythmias. •In patients with a systemic right ventricle•Heart rate variability (HRV) is reduced.•HRV correlates with systemic RV function and exercise capacity.•Reduced HRV correlates with supraventricular arrhythmias (SVT).•HRV may provide indirect information about outcome.